Initial temperature and extent of chemical equilibration of partons in relativistic collisions of heavy nuclei. (5th December 2017) - Srivastava, Dinesh K; Chatterjee, Rupa; Mustafa, Munshi G
Abstract: We study the consequences of a premise that, if a thermalized and chemically equilibrating quark gluon plasma is formed in relativistic collisions of heavy nuclei, then a knowledge of energy and entropy densities of the plasma fixes the initial temperature and the product of gluon fugacity and formation time uniquely, provided we know the relative fugacities of quarks and gluons. Thus, a smaller formation time would imply a larger fugacity, independent of the initial temperature. Next, we explore the limits of chemical equilibration of partons during the initial stages in relativistic collisions of heavy nuclei. Experimentally measured rapidity densities of transverse energy and charged particle multiplicities at RHIC and LHC energies are used to estimate energy and number densities with the assumption of the formation of a kinetically equilibrated plasma that may not be chemically equilibrated for quarks and gluons. The estimates are found to be very sensitive to the correction factor used to multiply the Bjorken energy density to get the initial energy density. The evolution of the chemical equilibration during the quark gluon plasma phase is inferred by solving master equations, including the processes gg ↔ ggg and gg ↔ q q ̄ along with expansion and cooling of the plasma. Possible consequences for the invariant mass distribution of intermediate mass dileptons radiated from the plasma are discussed.